2016
DOI: 10.1186/s12864-016-3024-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of differentially expressed genes in the floral transition of the summer flowering chrysanthemum

Abstract: BackgroundChrysanthemum is a leading cut flower species. Most conventional cultivars flower during the fall, but the Chrysanthemum morifolium ‘Yuuka’ flowers during the summer, thereby filling a gap in the market. To date, investigations of flowering time determination have largely focused on fall-flowering types. Little is known about molecular basis of flowering time in the summer-flowering chrysanthemum. Here, the genome-wide transcriptome of ‘Yuuka’ was acquired using RNA-Seq technology, with a view to she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
(68 reference statements)
2
25
0
Order By: Relevance
“…Among them, 34,605 unigenes were assigned a specific or general function on the basis of comparison against sequences in the nr, Swiss-Prot, KEGG, COG and GO databases, corresponding to approximately 54.19% of the total unigenes. This value is similar to that in C. morifolium ‘Fenditan’ (47%) 16 , C. morifolium ‘Yuuka’ (60%) 17 and C. lavandulifolium (53%) 28 based on an equivalent strategy of transcriptome analysis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among them, 34,605 unigenes were assigned a specific or general function on the basis of comparison against sequences in the nr, Swiss-Prot, KEGG, COG and GO databases, corresponding to approximately 54.19% of the total unigenes. This value is similar to that in C. morifolium ‘Fenditan’ (47%) 16 , C. morifolium ‘Yuuka’ (60%) 17 and C. lavandulifolium (53%) 28 based on an equivalent strategy of transcriptome analysis.…”
Section: Discussionsupporting
confidence: 79%
“…In C. morifolium ‘Fenditan’, a large number of transcription factors and structural genes involved in the photoperiod pathway as well as flower organ determination have been identified from whole transcriptome data by using the RNA-Seq technology 16 . Meanwhile, a transcriptome analysis of another cultivar C. morifolium ‘Yuuka’ succeeded in identifying many differentially expressed genes under the treatment of various daylengths 17 . While this technology has been intensively applied for studying flowering-time regulation in ornamental C. morifolium cultivars, but to our knowledge, no transcriptomic analysis regarding the flavonoid biosynthesis has been reported in medicinal C. morifolium cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In autumn‐flowering, chrysanthemum flowering time is majorly regulated by the photoperiod pathway under SD, and the GA signalling pathway predominated for flowering under LD (Dong et al , ), while the antiflorigen function of AFT under LD obligates the flowering only under SD (Higuchi et al , ). In summer‐flowering chrysanthemum, flowering might be promoted by the photoperiod and GA pathways under SD, and by the T6P and sugar signalling pathways under LD, while the flowering time is delayed by PHYB under LD (Ren et al , ). In our study, it was revealed CmFTL1 regulated flowering time in cv.…”
Section: Discussionmentioning
confidence: 99%
“…Using high-throughput sequencing, researchers have altered our view of the extent and complexity of eukaryotic transcriptomes, facilitated the discovery of novel genes (Qi et al 2012 ; Wang et al 2009 ). For example, several differentially-transcribed genes related to floral transition were identified in Chrysanthemum by Illumina sequencing (Ren et al 2016 ). Harrop et al ( 2016 ) used gene expression profiling to analyze genes that participated in reproductive meristem development in early rice inflorescences (Harrop et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%